Calculated electronic properties of ordered alloys - Moruzzi, V. L (World Scientific, 1995)
Includes bibliographical references (p. xi) and index; This is a handbook of calculated electronic properties of elements and of 3d/3d and 4d/4d ordered alloys. The book derives the ground-state or equilibrium properties of the metallic elements in both bcc and fcc structures, and of existing and nonexisting ordered binary transition-metal alloys in CsCl, CuAu, and Cu3Au structures by the analysis of binding curves, or total energy vs. volume curves, calculated from first-principles augmented-spherical-wave methods. The calculated properties, energy bands along symmetry lines in the respective Brillouin zones, and the total and I-decomposed density-of-states for each constituent is presented in a convenient single-page format. The calculated quantities presented include lattice constants, total energies, bulk moduli, potential at the nucleus, and charge densities at the nucleus and in the interstitial regions